One-Pot Sequence for Reductive-Acetylation of Carbonyl Compounds with (N-Methylimidazole)(tetrahydroborato)zinc Complex - Setamdideh, Davood; Khezri, Behrooz (Asian Journal of Chemistry, 2010)
Reductive-acetylation of variety of aliphatic and aromatic aldehydes and ketones, a,b-unsaturated carbonyl compounds are examined efficiently with (N-methylimidazole)(tetrahydroborato)- zinc complex, [Zn(BH4)2(nmi)], under mild condition in THF at room temperature or reflux conditions. The corresponding acetates were obtained in excellent yields (90-98 %).